Om Landmandsforsamlingernes fremtidige Ordning. Diskussion, d. 14de Decbr, 1870. - Møller-Holst, E. (Tidsskrift for Landøkonomi, 2018)
Om Landmandsforsamlingernes fremtidige Ordning. Diskussion, d. 14de Decbr, 1870.